Overreaction modeling of Stock Market through Intraday OHLC Prices - saied madadi; nages barzgar; mir hosein mousavi (پژوهش‌های تجربی حسابداری, 2014)
The Stock Market is Largely Influenced by the Flow of News and Information. In an Efficient Stock Market, Reaction of Investors to the News and Information appears to be a Correct Response. While in an Inefficient Stock Market, Reaction of Investors seems to be Overreaction or Underreaction. Neither in Overreaction nor Underreaction, Stock Price is being Defined Correctly. Through Overreaction modeling of Stock Market processed by Intraday OHLC Prices, which Refer to Open, High, Low, and Close Stock Prices, it is proven that Stock Market Price shows a Geometric Brownian Motion. Then Overreaction and Underreaction is shown to be identified through recognizing the Standardized Volatility Distribution. Furthermore, Discontinuous Flow of News and Information is introduced to extend the Model with more Realistic Assumptions. Two Statistics and Hypotheses are then organized in order to test the Overreaction into good and bad News; ultimately, to ascertain the Results not affected by the Heteroscedasticity, Hypotheses need to be tested again by the Modified Statistics.